Practice patterns and approach to kidney biopsy in lupus: a collaboration of the Midwest pediatric nephrology consortium and the childhood arthritis and rheumatology research alliance - Wenderfer, Scott E. (Pediatr Rheumatol Online J, 2015)
BACKGROUND: There is no clear consensus regarding optimal indications or timing of initial or repeat kidney biopsy in the management of pediatric systemic lupus erythematosus (pSLE). METHODS: A web-based survey was designed to assess current practice patterns among pediatric nephrologists and pediatric rheumatologists and distributed to members of Midwest Pediatric Nephrology Consortium (MWPNC) and Childhood Arthritis and Rheumatology Research Alliance (CARRA). RESULTS: Respondents included 111 rheumatologists and 71 nephrologists from 65 and 34 centers, respectively. Numbers of years in sub-specialty practice were comparable. Rheumatologists and nephrologists frequently collaborate in the care of children with lupus nephritis (LN). More than 90 % of respondents refer patients to each either other after diagnosing LN. Over 60 % describe shared decision making regarding when to perform kidney biopsy and how to interpret biopsy findings. Many pediatric nephrologists consider biopsy to be of higher risk for complication in pSLE and alter their standard pre-or post-biopsy management. CONCLUSIONS: It is uncommon for pediatric nephrologists to manage LN without input from pediatric rheumatologists and vice versa. Consensus exists between specialties in general, and practice differences that exist occur between individual physicians rather than between specialties. A systematic approach to biopsy may result in improved health related outcomes in pSLE. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12969-015-0024-x) contains supplementary material, which is available to authorized users.